(untitled) (Journal of history, 2023)
The system of archival laws and regulations of China is a single set of archival laws, archival administrative laws and regulations, local archival laws and regulations, archive administrative regulations of departments under the State Council, and local archival administrative regulations, all of which are interconnected and coordinated with each other, and the core is the "Law on Archives". The creation of a system of normative documents on archival affairs and rules contributes to an increase in the level of planning, science and foresight of archival laws, rules and amendments, and is also of great importance for promoting a unified archival legislation and ensuring a comprehensive, coordinated and sustainable development of the archival industry. This paper focuses on two aspects of electronic document management rule construction: examining the current situation and exploring strategic directions. This paper focuses on putting forward a series of principles and suggestions for the construction of China’s electronic document management rules in the new environment by analyzing the drawbacks of China’s electronic document management rule construction, pointing out that the construction of China’s electronic document management rules should strengthen the validity of electronic documents, fill gaps in existing rules, strengthen the coordination among rules, strengthen the construction of electronic document management standards In addition, attention should be paid to the research and publicity of electronic document management rules, and study the successful legislative experience of developed countries, in order to promote the construction of electronic document management rules in China. Key words: regulatory documents, archives, legislative bases, China, law.